ANALISIS KONSUMSI KOPI MERAPI DI D.I. YOGYAKARTA - Eko Nurrohman; Susi Widiatmi (Fakultas Pertanian UST, 2018)
The research had been held in Merapi coffee shop that located in tourist village of Petung, sub-district of Cangkringan, district of Sleman, Province of Yogyakarta. Oak shop that located in K.H Wahid Hasyim Number 50, Condong Catur, sub-district of Depok district of Sleman. And Turi – turi coffee that located in the side of Kaliaji, this research held on this June 2018, the purpose of the research is to knowing analysis of the consumption of the Merapi’s coffee in Yogyakarta. The method of this research is using a descriptive. With the purposing sampling. The determination of the respondence are using the 30 samples.Method of research itself is the double regression, test F and test T. from the research itself showing that the regression of the taste (X1), competitor (X2), serving (X3), price (X4), income (X5), and the type coffee (Dummy) itself influencing significantly to the consumer attraction. Through the test of t which is the variable of the competitor (X2), serving (X3) influence but not a big involvement toward the consumer attraction and the variable of the taste (X1), income (X5), and type of the coffee (dummy) influence significantly to the variable of attraction and price (X4) not influence the consumption of the Merapi coffee shop.